Managing Employee Motivation: Exploring the Connections Between Managers' Enforcement Actions, Employee Perceptions, and Employee Intrinsic Motivation. Issue 2 (3rd April 2017) - Mikkelsen, Maria Falk; Jacobsen, Christian Bøtcher; Andersen, Lotte Bøgh
ABSTRACT: A number of studies show that the use of external interventions such as command systems and economic incentives can decrease employee intrinsic motivation. Our knowledge of why the size of "the hidden cost of rewards" differs among organizations is, however, still sparse. In this article, we analyze whether local managers—the primary enforcers of external interventions—affect how employees perceive a command system and thereby affect employee intrinsic motivation. Using a multilevel dataset of 1, 190 teachers and 32 school principals, we test whether principals' use of "hard, " "mixed, " or "soft" actions to enforce a command system (obligatory teacher-produced student plans) is associated with teacher intrinsic motivation. Results show that teachers experiencing "hard" enforcement actions have lower intrinsic motivation than teachers experiencing "soft" enforcement actions. As expected by motivation crowding theory, part of this association is mediated by teachers' student plan requirement perception. These findings support the motivation crowding argument that employee intrinsic motivation depend on the employees' need for self-determination.